Transforming China :globalization, transition and development (China in the 21st Century) - Nolan, Peter (London, 2004)
These essays both enhance an understanding of China's immense success in meeting these challenges in the past and provide an indication of the challenges that still lie ahead. China's system reforms have been described as 'groping for stones to cross the river'. The journey across the river is far from over, and the other bank is only dimly visible.
Keywords: Economic development